PENGEMBANGAN DESAIN PELATIHAN UNTUK MENINGKATKAN KOMPETENSI GURU PRODUKTIF BIDANG TEKNOLOGI REKAYASA - Dina Dwi Aprilia; Riswandi Riswandi; Sugiyanto Sugiyanto (Akademika : Jurnal Teknologi Pendidikan, 2023)
The purpose of this research is to design training to increase teacher competence in implementing the teaching factory learning model for vocational teachers who teach at several SMK Negeri Center of Excellence in the North Lampung region and to review the effectiveness of the training designs developed. This type of research uses methods and development (R & D) with the ADDIE development model. The population is all productive teachers who teach at SMK Negeri 3 Kotabumi and SMK Negeri 1 Abung Selatan with a total of 60 teachers and a sample of 40 teachers for testing the resulting product development. Data collection was carried out using observation, survey and pretest - posttest techniques. Data analysis techniques were carried out using descriptive analysis including product feasibility analysis, product attractiveness analysis and teacher competency level analysis. The results of the research show that the products developed are feasible and attractive and can improve teacher competence